The Participation of National Minorities in Pre-Modern Educational Systems - Ruano, Carlos R. (Education Policy Analysis Archives, 2001)
This article presents the results of research carried out on the linguistic and educational needs of Guatemala's national minorities and the responses given to those needs by Guatemala's central government. Specifically, the case of the Garífuna population on the Atlantic Coast is studied with a view to understanding the educational policy dynamics underlying Pre-Modern States towards the multicultural groups' lack of participation and incorporation into the national polity. Lastly, the specific educational claims of the Garífunas are studied, particularly in relation to Guatemala's other linguistic blocks, namely, Mayan and Spanish language speakers.